2023
DOI: 10.1002/aocs.12745
|View full text |Cite
|
Sign up to set email alerts
|

Determining the structure and stability of essential oil‐sunflower wax and beeswax oleogels

Hatice Çokay,
Mustafa Öğütcü

Abstract: In this study, essential oil oleogels were produced using eucalyptus, lavender, lemon peel and tea tree oils with sunflower and beeswax. The physicochemical, thermal, textural, and structural features of the oleogels were determined. For the essential oils used, an addition level of less than 15% of beeswax (BW) was insufficient to form stable oleogels, whereas an addition level of 10% of sunflower wax (SW) was sufficient to form stable oleogels. The acid and peroxide values of the gels were higher than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Excluding the initial mass loss at 150–200 °C, which is around 5%, as a result of water evaporation, another essential range is that oleogel decomposition took place in two well-defined stages. Therefore, the first stage (also known as the main stage) occurred between 295 and 480 °C due to the decomposition of the part of the oleogel molecules that depends on the percentage of saturated and unsaturated fatty acids present in the mass of total fat [ 35 ]. Moreover, this stage is also associated with the thermal volatilization of the vegetable oil used for the formulation of the oleogels [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Excluding the initial mass loss at 150–200 °C, which is around 5%, as a result of water evaporation, another essential range is that oleogel decomposition took place in two well-defined stages. Therefore, the first stage (also known as the main stage) occurred between 295 and 480 °C due to the decomposition of the part of the oleogel molecules that depends on the percentage of saturated and unsaturated fatty acids present in the mass of total fat [ 35 ]. Moreover, this stage is also associated with the thermal volatilization of the vegetable oil used for the formulation of the oleogels [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Han et al 12 reported the crystallization kinetics of beeswax oleogels prepared with different oils, calculated with the Avrami model, the k value increasing with increasing proportion of linolenic acid. Most recently, Çokay and Öğütcü 13 reported beeswax and sunflower wax oleogels prepared with different EOs (citrus, tea tree, eucalyptus and lavender oils). In that study, the researchers indicated that volatile adsorption capacities and the critical gelation concentration of the waxes were different.…”
Section: Introductionmentioning
confidence: 99%